2004
DOI: 10.1111/j.1600-051x.2004.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Dentine hypersensitivity: a randomised, double‐blind placebo‐controlled study of the efficacy of a fluoride‐sensitive teeth mouthrinse

Abstract: The placebo response has again been shown to play a significant role in DH clinical trials and narrows the range over which to detect treatment differences. Study designs to minimise or prevent the placebo response in DH seem worthy of consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 22 publications
1
43
0
4
Order By: Relevance
“…Other clinical studies, 16,17 on the other hand, reported good DH treatment effects of using fluoride. Fluoride appears to be a subject of some debate with regard to the mechanism and effect of DH treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Other clinical studies, 16,17 on the other hand, reported good DH treatment effects of using fluoride. Fluoride appears to be a subject of some debate with regard to the mechanism and effect of DH treatment.…”
Section: Discussionmentioning
confidence: 99%
“…28,30 Because it is an unstable compound, CaF 2 rapidly dissociates after applica-tion, so that the anti-hyperesthesia effect is of short duration. In spite of fluoride being recognized as an effective anti-caries agent, its use as a desensitizing agent is still reported as unsuccessful when compared to therapeutic agents such as Gluma or Seal& Protect, despite its distinct modes of action.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,12,20,30 Because it is a painful and subjective phenomenon, the pain from the cervical lesion may be modified by the subject's emotional components. 23,24 Taking into consideration the effectiveness of the agents used, it is observed that each agent has advantages and disadvantages, in relation to cost and time consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Iontophoresis with 2% sodium fluoride [15] Desensitizing toothpastes/dentifrices [13,14] containing strontium salts, fluorides, formaldehyde, potassium salts like potassium nitrate [16], potassium chloride or potassium citrate [17] Nova Min Mouthwashes containing potassium nitrate and sodium fluoride [18,19], potassium citrate or sodium fluoride [20] or a mixture of fluorides [21]. …”
Section: In-office Agents At-home Agentsmentioning
confidence: 99%